Linguistic relativity today - Danesi, Marcel, 1946- author.
1 online resource (x, 160 pages)
Keywords: "This is the first textbook on the linguistic relativity hypothesis, presenting it in user-friendly language, yet analyzing all its premises in systematic ways. The hypothesis claims that there is an intrinsic interconnection between thought, language, and society. All technical terms are explained and a glossary at the back is provided. The book looks at the history and versions of the hypothesis, including the research paradigms and critiques that this notion has generated. It describes work on testing its validity in various domains, from grammar to discourse and artificial languages. It also extends the notion to other forms of relativity, from semiotic relativity to discursive relativity. Overall, it presents a comprehensive overview of the hypothesis, with pedagogical activities in each chapter, including questions for discussion and practical exercises on various notions. The book also examines the hypothesis as a foundational notion for the establishment of linguistic anthropology. This essential course text inspires creative, informed dialogue and debate for students of anthropology, linguistics, cultural studies, cognitive science, and psychology"--